Navigating the Legal Landscape: An Analysis of NFTs Under Armenian Law - Davtyan, Tatevik (Bulletin of Yerevan University C: Jurisprudence, 2023)
This article discusses the legal nature and features of non-fungible tokens (NFTs). The legislation of the Republic of Armenia does not regulate relations with irreplaceable marks. This article presents the legal status of NFTs and their possible place among the objects of civil rights defined by Article 132 of the RA Civil Code. The process of tokenization and its connection with the right of ownership is analyzed. The norms of intellectual property legislation are analyzed, and it is concluded that the buyer of NFTs representing an object of intellectual property does not automatically acquire intellectual property rights to the object: these rights can be transferred to the buyer of NFTs through smart contracts or traditional legal instruments. The possibility of implementing smart contracts in Armenia is analyzed in the absence of special regulations for smart contracts.